Adolescent transition to adult care for HIV-infected adolescents in Kenya (ATTACH): study protocol for a hybrid effectiveness-implementation cluster randomised trial. Issue 12 (2nd December 2020) - Njuguna, Irene N; Beima-Sofie, Kristin; Mburu, Caren W; Mugo, Cyrus; Neary, Jillian; Itindi, Janet; Onyango, Alvin; Richardson, Barbra A; Rubin Means, Arianna; Sharma, Monisha; Weiner, Bryan J; Wagner, Anjuli D; et al.
Abstract : Introduction: Successfully transitioning adolescents to adult HIV care is critical for optimising outcomes. Disclosure of HIV status, a prerequisite to transition, remains suboptimal in sub-Saharan Africa. Few interventions have addressed both disclosure and transition. An adolescent transition package (ATP) that combines disclosure and transition tools could support transition and improve outcomes. Methods and analysis: In this hybrid type 1 effectiveness-implementation cluster randomised controlled trial, 10 HIV clinics with an estimated ≥100 adolescents and young adults age 10–24 living with HIV (ALWHIV) in Kenya will be randomised to implement the ATP and compared with 10 clinics receiving standard of care. The ATP includes provider tools to assist disclosure and transition. Healthcare providers at intervention clinics will receive training on ATP use and support to adapt it through continuous quality improvement cycles over the initial 6 months of the study, with continued implementation for 1 year. The primary outcome is transition readiness among ALWHIV ages 15–24 years, assessed 6 monthly using a 22-item readiness score. Secondary outcomes including retention and viral suppression among ALWHIV at the end of the intervention period (month 18), implementation outcomes (acceptability, feasibility, fidelity, coverage and penetration) and programme costs complement effectiveness outcomes. The primary analysis will be intent to treat, using mixed-effects linear regression models to compare transition readiness scores (overall and by domain (HIV literacy, self-management, communication, support)) over time in control and intervention sites with adjustment for multiple testing, accounting for clustering by clinic and repeated assessments. We will estimate the coefficients and 95% CIs with a two- sided α=0.05. Ethics and dissemination: The study was approved by the University of Washington Institutional Review Board and the Kenyatta National Hospital Ethics and Research Committee. Study results will be shared with participating facilities, county and national policy-makers. Trials registration number: NCT03574129; Pre-results .